2011
DOI: 10.1177/1464884910388227
|View full text |Cite
|
Sign up to set email alerts
|

Media and foreign policy: A comparative study of journalists’ perceptions of press—government relations during the six-party talks

Abstract: This study examines journalists’ role conceptions in their coverage of diplomatic issues, based on a survey of South Korean, US, and European journalists who covered the six-party talks on North Korea’s nuclear program. The author found differences between South Korean, US, and European journalists in their perceptions of the role of journalists in the multilateral nuclear talks. Compared with US and European journalists, South Korean journalists believed more strongly that journalists are participants in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Countries resort to the mass media to create channels of communication with parties that cannot communicate directly with them, and governments use the mass media to reinforce their positions before the governments of other countries to control the climate of negotiations. the statesmen can send signals through the media if they are unsure of the way the other country will respond to natural negotiation [6].…”
Section: The Importance Of the Media To Political Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Countries resort to the mass media to create channels of communication with parties that cannot communicate directly with them, and governments use the mass media to reinforce their positions before the governments of other countries to control the climate of negotiations. the statesmen can send signals through the media if they are unsure of the way the other country will respond to natural negotiation [6].…”
Section: The Importance Of the Media To Political Systemsmentioning
confidence: 99%
“…The study also concluded that the most important thing that distinguishes the Egyptian president Al-Sadat's rule regarding the political decision-making process is that it was an individual decision whether it is related to the internal policy or foreign policy. According to the study, President Sadat viewed himself as everything [20] Journalists' perception of the limits of their roles is reflected in how they cover events [6]. Their perceptions play an important role in drafting the news release decision as well as the selection of sources, and that journalists' choices are later an indicator of countries' foreign policy.…”
Section: The Role Of the Press Editor In The Political Decision-makin...mentioning
confidence: 99%